Gambaran Pengetahuan Siswa SMK YPKK 1 Sleman Terhadap Penggunaan Obat Tradisional - Nugrahini, Febrina; Setiawati, Rini (UKInstitute, 2024)
This study aims to evaluate the knowledge level of students at SMK YPKK 1 Sleman regarding the use of traditional medicine. The study employs a descriptive quantitative approach with a cross-sectional design, involving 113 students from grades X, XI, and XII, who were purposively selected as the sample. Data were collected through a questionnaire that covered respondent characteristics, sources of information on traditional medicine, methods of obtaining it, forms of preparation, as well as knowledge and use of traditional medicine. The results indicate that the majority of students have good knowledge about traditional medicine (60%); however, the use of traditional medicine among students is relatively low, with 50% having a low level of usage. This study underscores the importance of increasing adolescent interest in traditional medicine to preserve cultural heritage and promote health.